Long‐term outcomes in patients with recurrent human papillomavirus‐positive oropharyngeal cancer after upfront transoral robotic surgery. Issue 12 (9th August 2020) - Su, William; Rajeev‐Kumar, Greeshma; Kang, Martin; Posner, Marshall; Liu, Jerry T.; Westra, William; Miles, Brett A.; Gupta, Vishal; Sharma, Sonam; Misiukiewicz, Krzysztof; Genden, Eric; Bakst, Richard L.
Abstract: Background: Clinical course following failure of human papillomavirus (HPV)‐positive oropharyngeal cancers (HPV + OPC) is poorly understood. This study aims to characterize disease course following failure after transoral robotic surgery (TORS). Methods: We identified patients with HPV + OPC‐treated upfront with TORS at our institution from 2007 to 2017. HPV status was confirmed with immunohistochemistry or HPV DNA polymerase chain reaction. Patient characteristics, treatment modalities, and post‐recurrence outcomes were analyzed for the recurrent cohort. Results: Of the 317 HPV + OPC patients, 28 (8.8%) experienced recurrence, all of HPV 16/18 subtypes. Median post‐recurrence survival was 19.8 months (range 2.3‐195.8 months) in the 12 locoregional and 16 months (range 2.4‐79.5 months) in the 14 distant failures. Sixteen are alive with a median of 39.8 months (range 5.5‐209.4 months) after retreatment. Conclusion: This is one of the largest series evaluating survival following TORS failure in HPV + OPC. Despite failure, long‐term survival and durable remission are possible with single‐modal or multiple‐modal salvage treatment.